1990
DOI: 10.1083/jcb.111.3.1081
|View full text |Cite
|
Sign up to set email alerts
|

Control of actin filament length by phosphorylation of fragmin-actin complex.

Abstract: Abstract. Fragmin is a Ca2÷-sensitive F-actin-severing protein purified from a slime mold, Physarum polycephalum (Hasegawa, T., S. Takahashi, H. Hayashi, and S. Hatano. 1980. Biochemistry. 19:2677-2683. It binds to G-actin to form a 1:1 fragmin/actin complex in the presence of micromolar free Ca 2+. The complex nucleates actin polymerization and caps the barbed end of the short F-actin (Sugino, H., and S. Hatano. 1982. Cell Motil. 2:457-470). Subsequent removal of Ca 2÷, however, hardly dissociates the compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 30 publications
2
25
0
Order By: Relevance
“…It has been shown previously that phosphorylation of Dictyostelium actin plays a role in assembly/disassembly of the actin cytoskeleton (Furuhashi and Hatano, 1990;Howard et al, 1993). In addition, it was recently found that yeast actin is phosphorylated (Futcher et al, 1999).…”
Section: How Does Ssk2p Promote Actin Reassembly?mentioning
confidence: 96%
“…It has been shown previously that phosphorylation of Dictyostelium actin plays a role in assembly/disassembly of the actin cytoskeleton (Furuhashi and Hatano, 1990;Howard et al, 1993). In addition, it was recently found that yeast actin is phosphorylated (Futcher et al, 1999).…”
Section: How Does Ssk2p Promote Actin Reassembly?mentioning
confidence: 96%
“…In previous studies the purified fragmin-actin complex was not phosphorylated following incubation with ATP alone [6]. In the present work, fragmin-actin complex was purified by a new purification procedure in which ammonium sulfate precipitation for concentrating proteins was omitted.…”
Section: Resultsmentioning
confidence: 87%
“…Thus, the fragmin-aetin complex purified by the new method was inactivated by incubation with ATP alone. We have demonstrated that the phosphorylation of actin of the fragrnin-actin complex by aetin kinase is responsible for inactivation of the complex [6,8,9]. Because there is a possibility that the inactivation of the complex incubated with ATP alone is due to phosphorylation of actin of the complex by actin kinase, the complex was incubated with [y-32P]ATP and subjected to SDS-PAGE, followed by autoradiography.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations